Optimization of Abrasive Water Jet Turning Parameters for Machining of Low Density Polyethylene Material Based on Experimental Design Method - Kartal, F.; Çetin, M. H.; Gökkaya, H.; Yerlikaya, Z. (Walter de Gruyter GmbH, 2014)
Abstract Studies to improve the machining of engineering materials have great importance for mechanical systems. Abrasive water-jet turning (AWJT) is a new and effective process for increasing machinability of engineering materials by providing temperature free cutting conditions, high surface quality and having no tool wear problem. In this study, AWJT of low density polyethylene (LDPE) material were investigated in terms of average surface roughness (ASR) and material removal rate (MRR) values and process parameters were optimized by experimental design method. The primary objectives of the study are to investigate AWJT process and system parameters to enhance machinability of LDPE material and to determine optimal processing parameters. Nozzle feed rate (5, 25 and 45 mm/min), abrasive flow rate (50, 200 and 350 g/min) and spindle speed (1 000, 1 500 and 2 500 min−1) were analyzed as process parameters. Taguchi L27 orthogonal full factorial design, optimization box and analysis of variance (Anova) were used for the experimentation and results analysis. Experimental results show that, AWJT process is more efficient in the machining of LPDE material than the conventional machining methods by increasing surface quality and MRR parameters. Minimum ASR and maximum MRR were obtained 1.67 μm and 14 072.02 mm3/min respectively; at optimum parameters of 5 mm/min nozzle feed rate, 350 g/min abrasive flow rate and 2 500 min−1 spindle speed.
Keywords: 3. Good health